Retroregulation of the int gene of bacteriophage lambda: control of translation completion. - Schindler, D (1981)
Bacteriophage lambda regulates the integration--excision reaction as a crucial aspect of the choice of pathway during lysogenic or lytic viral development. This control involves differential expression of the tightly linked, partially overlapping int and xis genes from two promoter sites: pI, positively regulated by cII/cIII proteins, and pL, positively regulated by N protein. After lambda infection, Int is synthesized from the pI transcript under cII regulation; however, very little Int is produced from the pL RNA because of the existence of a cis-acting regulatory element, sib, on the opposite side of the int gene from the pL promoter. Presumably sib serves to prevent unwanted synthesis of Int protein during the lytic response; the Int protein necessary for excisive recombination from a prophage can be supplied by pL transcription because sib is separated from int by prophage insertion. We have studied the effect of sib on nearby lambda genes by means of gel electrophoresis of labeled proteins from infected cells. Deletion of the sib region greatly enhances production of Int protein without substantial effect on Xis production; thus, sib regulation normally is highly specific for Int. When the sib region is moved past int and xis by deletion, regulation of the adjacent gene for the protein Ea22 occurs, suggesting that sib regulation can work on other genes. Although synthesis of wild-type Int is severely inhibited by sib, shorter Int protein fragments generated by nonsense mutations escape sib regulation, indicating that the regulation is translational and occurs near the completion stage of protein synthesis. Regulation by sib thus exhibits novel regulatory features: distal location, recombinational control, and regulation of the completion of protein synthesis. Because Int and Ea22 control is lost in a RNase III- host, we suggest that sib regulation might involve RNase III cleavage of a RNA duplex region that includes sib and the regulatory target (normally the int gene). We note such a potential site within int.